A rare case of caseous necrosis of mitral valve - Deepti Naik,; Sanjaya Viswamitra, (Asian Journal of Medical Sciences, 2024)
Caseous calcification of the mitral annulus, an uncommon kind of intracardiac mass, is a form of degenerative disease that afflicts the mitral valve causing liquefactive or caseous necrosis. Caseous calcification of mitral annulus is rarely encountered in practice; however, it should be on the list of differential diagnosis of any intracardiac masses located close to the mitral annulus.